2012
DOI: 10.1002/ptr.4743
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of an Antiosteoporosis Herbal Formula Containing Epimedii Herba, Ligustri Lucidi Fructus and Psoraleae Fructus on Density and Structure of Rat Long Bones Under Tail‐Suspension, and its Mechanisms of Action

Abstract: An innovative anti-osteoporosis herbal formula containing epimedii herba, ligustri lucidi fructus and psoraleae fructus (ELP) has been previously shown its bone protecting effects in ovariectomized osteoporotic rats and also in post-menopausal osteopenic women. This study aimed to investigate the efficacy of ELP against bone loss during physical inactivity or weightlessness. A hindlimb unloading tail-suspended rat model was used for studying the effects of ELP on bone mineral density (BMD) and bone micro-archi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 32 publications
2
25
0
1
Order By: Relevance
“…These studies demonstrated the loss of bone mineral density resulting from weightlessness could be reduced while phytotherapy was administered during the tail suspension period [7]. The exact mechanisms are not known but it is assumed that boostering of osteoblastic activities could be the explanation [8,9].…”
Section: Platform Studiesmentioning
confidence: 99%
“…These studies demonstrated the loss of bone mineral density resulting from weightlessness could be reduced while phytotherapy was administered during the tail suspension period [7]. The exact mechanisms are not known but it is assumed that boostering of osteoblastic activities could be the explanation [8,9].…”
Section: Platform Studiesmentioning
confidence: 99%
“…In the clinical TCM practice, FLL is a component among kidney-tonifying herbal formulae for the treatment of osteoporosis (Sun et al, 2008;Zhang et al, 2008a;Siu et al, 2013). Our previous study revealed that the crude extract of FLL could improve calcium balance by regulating transcellular calcium absorption in intestine and reabsorption in kidney (Zhang et al, 2006(Zhang et al, , 2008b(Zhang et al, , 2008c, consequently exerting bone-sparing function in aged female rats and aged osteoporotic rats with estrogen deficiency (Zhang et al, 2008d;Dong et al, 2014).…”
Section: Introductionmentioning
confidence: 97%
“…Fructus Ligustri Lucidi (FLL), the fruit of Ligustrum lucidum Ait, is a commonly prescribed herb to nourish the endocrine and renal systems and to strengthen the bones in Traditional Chinese Medicine (TCM) (Zhang et al, 2008b;Siu et al, 2013). In the clinical TCM practice, FLL is a component among kidney-tonifying herbal formulae for the treatment of osteoporosis (Sun et al, 2008;Zhang et al, 2008a;Siu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is a need to seek alternative and effective treatment alternatives for osteoporosis. Clinical practice has shown a bright future for Chinese herbal medicine and Chinese herbal formulas in treating osteoporosis 11,12…”
Section: Introductionmentioning
confidence: 99%